The IOI is (not) a Science Olympiad - Tom VERHOEFF (Informatics in Education, 2006)
The International Olympiad in Informatics (IOI) aspires to be a science olympiad alongside such international olympiads in mathematics, physics, chemistry, and biology. Informatics as a discipline is well suited to a scientific approach and it offers numerous possibilities for competitions with a high scientific standing. We argue that, in its current form, the IOI fails to be scientific in the way it evaluates the work of the contestants.